How Much Does Globalisation Affect the Income Inequality in Romania? - Neagu, Olimpia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
The paper examines the connection between income inequality and globalisation in the case of Romania. Using World Bank data and the KOF globalisation index we document that in Romania the increasing globalisation process has led to the growth of income inequality, during 1992-2011. Increasing dimensions of globalisation process has led to the deepening the gap between individuals' and households incomes in Romania.